KAJIAN USAHA RUMAH TANGGA BUDIDAYA BANDENG DI SULAWESI SELATAN TAHUN 2013 (Jurnal Aplikasi Statistika & Komputasi Statistik, 2021)
Since 2010-2013 milkfish production in Indonesia is the highest in the world. The highest milkfish production in Indonesia is in South Sulawesi. But the growth of milkfish production in the province from 2010-2012 decreased from 20.67% to 2.75%. This indicates that the milkfish cultivation business actors still do not maximize the input variables for milkfish production. This study aims to analyze the effect of land area, seed costs, fertilizer and drug costs, and labor costs on milkfish production, analyze Return to Scale, and analyze economies of scale in the province of South Sulawesi in 2013. The study uses multiple linear regression analysis methods. Based on the results of the analysis it is known that the area of ??land, the cost of seeds, the cost of fertilizers and medicines, and labor costs have a significant and positive effect on milkfish production in South Sulawesi in 2013. The milkfish cultivation business in South Sulawesi in 2013 was in the Increasing Return to Scale condition. The percentage of households that are in economies of scale is 69.53%.Keywords: multiple linear regression, return to scale, economies of scale, milkfish cultivation.